Modification of pyruvate kinase and lactate dehydrogenase in foot muscle of the sea mussel Mytilus galloprovincialis under anaerobiosis and recovery - V.I. Lushchak; T.V. Bahnjukova; A.V. Spichenkov (Brazilian Journal of Medical and Biological Research, 1997)
The modification of pyruvate kinase (PK) and lactate dehydrogenase (LDH) activity in foot muscle of the mussel Mytilus galloprovincialis during exposure to air and recovery in water was investigated. In the course of exposure to air, the activity of these enzymes measured at high and low substrate concentrations showed successive increases and decreases. Returning the mussels to water after exposure to air affected enzyme activity in a manner similar to anaerobiosis. When measuring at saturated concentrations of substrates and substrate and coenzyme for PK and LDH, respectively, the maximum activation of PK (37%) was observed at 4 h of animal exposure to air, and for LDH (67%) at 6 h exposure to air. During 24 h of exposure of animals to air, PK activity practically reached the stock level, while LDH was still activated (148%). The change in lactate dehydrogenase activity in mussel muscle during anoxia and recovery is described here for the first time. Variation in pyruvate kinase activity during exposure to air and recovery is linked to the alteration of half-maximal saturation constants and maximal velocity for both substrates. The possible role of reversible phosphorylation in the regulation of pyruvate kinase and lactate dehydrogenase properties is discussed